Análise comparativa de estruturas de pavimentos utilizando RCD e dimensionadas a partir de parâmetros distintos - Pereira, Letícia Azevedo de Farias (2021)
The growing demand for aggregates for the construction of highways has boosted the study of construction and demolition waste (RCA or CD&W), applied to pavements. With the implementation of DNIT's new pavement dimensioning method (software MeDiNa), it becomes important to carry out resilience modulus (MR) and permanent deformation (DP) tests of the most varied types of materials used in paving. In this dissertation, designs of flexible pavement structures developed considering two different methods are presented, which make use of the modulus of resilience and permanent deformation and the California Bearing Ratio (CBR), and apply soil mixtures with RCA, and mixtures of soil-gravel in base layer and/or subbase, in order to develop a cost comparison between these methods and between materials. The soil, coming from the city of Ipueira/RN, was identified by the MCT assay as NG’, with nonlaterite behavior, the RCA and gravel used had nominal sizes of 19 mm. Mixtures of soil-gravel and soil-RCA were analyzed using aggregates in the percentages of 15%, 30%, 45% and 60%, by mass. Resilience modulus tests were carried out in all mixtures and permanent deformation in mixtures with soil-RCA in the proportion of 70% soil and 30% residue. The characterization and analysis of the mixtures showed that the proportions evaluated did not obtain an adequate fit in the working ranges proposed by DNIT for use in the base layer. The results obtained in the MR tests were satisfactory and the mixtures of soil-gravel 70-30 and soil-RCA 70-30 presented the highest values of average resilience modulus. The regression parameters (R²) obtained in the Statistica 10.0 software through the composite model executed based on the data from the resilience modulus tests, showed that the mixtures have a significant influence of the confinement and deviation stresses considered simultaneously. Based on the regression parameters, pavement structures designed with the MeDiNa software were proposed. The material selection criterion for the design using the CBR method made it impossible to use the soil-RCA 70-30 in the base layer, but in the design performed in the MeDiNa software it was found that this material can be used in base and sub-base layers, in certain design situations, since it was possible to obtain structures that met the fatigue and permanent deformation criteria for the useful life period.